Resistive switching mechanisms in BiFeO3 devices with YBCO and Ag as top electrodes - Santiago Ceballos Medina; Lorena Marín Mercado; Alexander Cardona-Rodríguez; Mario Fernando Quiñonez Penagos; César Magén; Luis Alfredo Rodríguez; Juan Gabriel Ramírez (Physics Open)
The resistive switching (RS) effect in ferroelectric oxides continues to attract significant attention due to its potential applications in nonvolatile memory and neuromorphic computing devices. In this study, we investigate the RS properties of BiFeO3/YBa2Cu3O7−d (BFO/YBCO) bilayers grown on LSAT substrates, comparing two different top-electrode materials: YBCO and Ag. The devices were fabricated using reactive sputtering at high oxygen pressure, and their RS mechanisms were investigated via current-voltage (I-V) measurements. We find all devices exhibit unipolar behavior, with symmetric RS behavior observed in devices with YBCO top electrodes and asymmetric RS in those with Ag top electrodes. Devices with YBCO top electrodes display ohmic conduction, whereas Ag top electrode devices exhibit a combination of Schottky, Poole-Frenkel emission, and spaced charge limited conduction mechanisms. Resistance versus time measurements were performed over 30 cycles with 20 different writing voltages to evaluate the ratio between the low resistance state (LRS) and high resistance state (HRS). Ag top electrodes devices consistently exhibited higher resistance ratios ‒approximately three times larger‒ compared to YBCO devices. Furthermore, better temporal stability of HRS and LRS was observed in devices with Ag top electrodes, attributed to the differences in the Fermi energy levels between YBCO, Ag and BFO. The superior performance of Ag top electrode devices, including their higher storage density and low operation parameters (0.25 V and 5 nA), highlights their potential for energy-efficient applications in future oxide-based memory and neuromorphic devices.